El Olvido - Honigmann, Heddy (Netherlands, 2008)
Oblivion is a film about waiters and bartenders in old Lima restaurants who are fighting a silent struggle against the decline of their lives and of their country. Survivors of the last forty years of the troubled history of Peru, they tell us what they did to survive the gigantic inflation, the corruption, the violence of Shining Path and that of the army in Peru. The documentary is framed by footage of repeated presidential promises made by Fujimori and Peréz, which are contrasted with the testimonies and experiences of the ordinary people in the country, as they strive to make enough for themselves and their families to get by. Sharp, tender, painful and funny stories are woven together in a documentary about pride and self-respect, love, politics, and society, crumbling in a world which is out of control.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films